2008
DOI: 10.1128/mcb.00304-08
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Posttranslational Mechanism for the Regulation of hERG1 K+ Channel Expression and hERG1 Current Density in Tumor Cells

Abstract: A common feature of tumor cells is the aberrant expression of ion channels on their plasma membrane. The molecular mechanisms regulating ion channel expression in cancer cells are still poorly known. K ؉ channels that belong to the human ether-a-go-go-related gene 1 (herg1) family are frequently misexpressed in cancer cells compared to their healthy counterparts. We describe here a posttranslational mechanism for the regulation of hERG1 channel surface expression in cancer cells. This mechanism is based on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
75
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 57 publications
(76 citation statements)
references
References 44 publications
1
75
0
Order By: Relevance
“…This suggests the existence of a tumor typerelated hERG1 isoform signature; (ii) hERG1A overexpression in gastric cancer correlates with an increased stability of the corresponding mRNA, in highly hERG1 expressing gastric cancer cells, a fact that candidates this as the mechanism underlying hERG1A overexpression in gastric cancer samples. Consistently, we excluded a significant contribution to hERG1 overexpression by the methylation status of the hERG1A promoters as well as of posttranslational mechanisms, based on the expression of the USO transcripts (20).…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…This suggests the existence of a tumor typerelated hERG1 isoform signature; (ii) hERG1A overexpression in gastric cancer correlates with an increased stability of the corresponding mRNA, in highly hERG1 expressing gastric cancer cells, a fact that candidates this as the mechanism underlying hERG1A overexpression in gastric cancer samples. Consistently, we excluded a significant contribution to hERG1 overexpression by the methylation status of the hERG1A promoters as well as of posttranslational mechanisms, based on the expression of the USO transcripts (20).…”
Section: Discussionmentioning
confidence: 73%
“…The relevance of posttranslational mechanisms was excluded, because no differences in the amount of the hERG1 USO protein (ref. 20; e.g., the main posttranslational mechanism affecting hERG1 protein levels) were detected ( Supplementary Fig. S5).…”
Section: Analysis Of Herg1 Expression In Primary Gastric Cancermentioning
confidence: 99%
“…To better distinguish these mechanisms, we expressed several mutant constructs in HEK cells: the nonconducting hERG1-G628S (38), hERG1-R531C, and hERG1-K525C, which are S4 domain mutants with altered activation (39), and the noninactivating hERG1-S620T (40). Flow cytometry analysis (41) indicated that the plasma membrane abundance of the mutants was~25 to 30% less compared to that of wild-type hERG1 (Fig. 4C).…”
Section: Kcne1 and B 1 Integrin Compete For Binding To Herg1mentioning
confidence: 99%
“…The human ether-à-go-go-related gene (hERG) is expressed in a number of tumor cell lines of various histogenetic origins, although is not present in the corresponding healthy cells, which indicates an association between hERG expression and the development of cancer (10)(11)(12). In a previous study by this group, it was identified that As 2 O 3 induces the apoptosis of MCF-7 breast cancer cells via inhibition of hERG channels (13).…”
Section: Introductionmentioning
confidence: 99%